2007
DOI: 10.1039/b703642f
|View full text |Cite
|
Sign up to set email alerts
|

Solvent extraction of U(vi) by task specific ionic liquids bearing phosphoryl groups

Abstract: A novel class of hydrophobic ionic liquids based on quaternary ammonium cation and bearing phosphoryl groups was synthesized. The preliminary results of U(VI) extraction from aqueous solution into the ionic liquid are presented.Room-temperature ionic liquids (RTILs) are promising alternative solvents for organic synthesis, catalysis, electrochemistry and extraction. 1 Among industrial processes, extraction and separation of actinides and lanthanides from nuclear waste is one of the most challenging fields. 2,3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 148 publications
(62 citation statements)
references
References 19 publications
0
62
0
Order By: Relevance
“…The possibility of using ILs instead of kerosene for extraction of uranium has been investigated. A series of studies were conducted by Giridhar et al for the extraction of uranium (U(VI)) from nitric acid (HNO 3 ) solution using TBP and ILs as diluents with direct electrodeposition of uranium from ILs phase [19][20][21][22][23][24][25] [23]. By using synthesized IL (1.1 M) in tri-n-butylmethyl ammonium bis(trifluoromethanesulphonyl) ([Me 3 NBu][Tf 2 N]), a remarkable distribution ratio for U(VI) (D U(VI) value of 170) was obtained.…”
Section: Recovery Of Uraniummentioning
confidence: 99%
“…The possibility of using ILs instead of kerosene for extraction of uranium has been investigated. A series of studies were conducted by Giridhar et al for the extraction of uranium (U(VI)) from nitric acid (HNO 3 ) solution using TBP and ILs as diluents with direct electrodeposition of uranium from ILs phase [19][20][21][22][23][24][25] [23]. By using synthesized IL (1.1 M) in tri-n-butylmethyl ammonium bis(trifluoromethanesulphonyl) ([Me 3 NBu][Tf 2 N]), a remarkable distribution ratio for U(VI) (D U(VI) value of 170) was obtained.…”
Section: Recovery Of Uraniummentioning
confidence: 99%
“…[13][14][15][16][17][18] However, they are expensive solvents and before any industrial applications can be envisioned, it is necessary to evaluate the exact contribution of RTILs compared with the "conventional" extraction systems. To do so, measurement of the extraction efficiency is just the first step.…”
Section: Introductionmentioning
confidence: 99%
“…Ionic liquids are under serious scrutiny as potential alternative solvents for the separation of radioactive elements for reuse or disposal because their properties can potentially improve process safety and efficiency. [18] The isotope 10 B, present in 20 % natural abundance, has a very high thermal neutron-capture cross-section. Calculations [19] have shown that ionic liquids with sufficiently high natural boron concentrations can be used as nuclear-processing media as they are inherently safe with regards criticality accidents.…”
mentioning
confidence: 99%